2012
DOI: 10.25225/fozo.v61.i1.a5.2012
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny of species and cytotypes of mole rats (Spalacidae) in Turkey inferred from mitochondrial cytochromebgene sequences

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
24
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 28 publications
5
24
0
Order By: Relevance
“…Which factor causes these rearrangements is still not conclusively known. On the other hand, recently published molecular studies (Krystufek et al, 2011;Hadid et al, 2012;Kandemir et al, 2012) showed that differentiation of chromosomal races of blind mole rats in Anatolia was already done and each chromosomal race might be a good candidate to be a separate species. However, more detailed molecular studies using techniques such as genome analysis and mtDNA are still required.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Which factor causes these rearrangements is still not conclusively known. On the other hand, recently published molecular studies (Krystufek et al, 2011;Hadid et al, 2012;Kandemir et al, 2012) showed that differentiation of chromosomal races of blind mole rats in Anatolia was already done and each chromosomal race might be a good candidate to be a separate species. However, more detailed molecular studies using techniques such as genome analysis and mtDNA are still required.…”
Section: Resultsmentioning
confidence: 99%
“…According to our parsimony tree results, N. xanthodon grouped polyphyletically, because the 2n = 56Tr (N. leucodon) grouped together with an Anatolian sample (N. xanthodon). Kandemir et al (2012) investigated the phylogeny of Turkish blind mole rats using molecular tools. They found similar tree topology.…”
Section: Chromosomal Evolution Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, in light of all the information that we know about Turkish mole rats, it can easily be seen that the taxonomic status of Turkish mole rat species and subspecies remains uncertain as some cytotypes have genetic differences on the species level (Nevo et al, 1995;Arslan et al, 2010;Kandemir et al, 2012). Therefore, the validity of the taxonomic status of all species and subspecies previously described from Turkey should be investigated to form a foundation for understanding taxonomic relationships.…”
mentioning
confidence: 99%
“…Only a limited number of genetic studies have been carried out on Turkish mole rat cytotypes. Phylogenetic studies using data from allozymes (Nevo et al, 1995), randomly amplified polymorphic DNA (Kankılıç et al, 2013), mitochondrial sequences (Arslan et al, 2010;Hadid et al, 2012;Kandemir et al, 2012;Kryštufek et al, 2012), and cytogenetics (Ivanitskaya et al, 2008;Arslan et al 2011) have been conducted in an attempt to understand relationships within Nannospalax. These molecular studies with limited cytotype sampling supported the monophyly of the genus and recognized 4 major clades (vasvarii, leucodon, xanthodon, and ehrenbergi) (Hadid et al, 2012).…”
mentioning
confidence: 99%